Tracing the Phonetic Space of Prosodic Focus Marking - Roessig, Simon; Winter, Bodo; Mücke, Doris (Frontiers in Artificial Intelligence, 2022)
Focus is known to be expressed by a wide range of phonetic cues but only few studies have explicitly compared different phonetic variables within the same experiment. We present re-sults from an analysis of 19 phonetic variables conducted on a data set of German that com-prises the opposition of unaccented (background) versus accented (in focus), as well as different focus types with the nuclear accent on the same syllable (broad, narrow, and con-trastive focus). The phonetic variables are measures of the acoustic and articulographic sig-nals of a target syllable. Overall, our results provide the highest number of reliable effects and largest effect sizes for accentuation (unaccented versus accented), while the differentiation of focus types with accented target syllables (broad, narrow and contrastive focus) are more subtle. The most important phonetic variables across all conditions are measures of funda-mental frequency. The articulatory variables and their corresponding acoustic formants re-veal lower tongue positions for both vowels /o, a/, and larger lip openings for the vowel /a/ under increased prosodic prominence with the strongest effects for accentuation. While dura-tion exhibits consistent mid-ranked results for both accentuation and the differentiation of fo-cus types, measures related to intensity are particularly important for accentuation. Further-more, voice quality and spectral tilt are affected by accentuation but also in the differentiation of focus types. Our results confirm that focus is realized via multiple phonetic cues. Addition-ally, the present analysis allows a comparison of the relative importance of different measures to better understand the phonetic space of focus marking.